Pathways of Methane Transformation over Copper‐Exchanged Mordenite as Revealed by In Situ NMR and IR Spectroscopy. (27th November 2019) - Sushkevich, Vitaly L.; Verel, René; van Bokhoven, Jeroen A.
Abstract: The reaction of methane with copper‐exchanged mordenite with two different Si/Al ratios was studied by means of in situ NMR and infrared spectroscopies. The detection of NMR signals was shown to be possible with high sensitivity and resolution, despite the presence of a considerable number of paramagnetic Cu II species. Several types of surface‐bonded compounds were found after reaction, namely molecular methanol, methoxy species, dimethyl ether, mono‐ and bidentate formates, Cu I monocarbonyl as well as carbon monoxide and dioxide, which were present in the gas phase. The relative fractions of these species are strongly influenced by the reaction temperature and the structure of the copper sites and is governed by the Si/Al ratio. While methoxy species bonded to Brønsted acid sites, dimethyl ether and bidentate formate species are the main products over copper‐exchange mordenite with a Si/Al ratio of 6; molecular methanol and monodentate formate species were observed mainly over the material with a Si/Al ratio of 46. These observations are important for understanding the methane partial oxidation mechanism and for the rational design of the active materials for this reaction. Abstract : Alles dreht sich um das Verhältnis : Die Reaktion von Methan mit Cu‐ausgetauschtem Mordenit mit zwei verschiedenen Si/Al‐Verhältnissen wurde mithilfe von In‐situ‐NMR und Infrarotspektroskopie untersucht. Die Struktur der aktiven Kupferzentren hat einen signifikanten Einfluss auf die relative Menge und die Art der Reaktionsprodukte.